Helicobacter spp. na saliva e mucosa gástrica de cães domésticos com e sem vômito crônico na região central do Rio Grande do Sul - Segundo, Daniel Dourado Guerra (2019)
Helicobacter pylori is a spiral-shaped bacterium frequently detected in the stomach of humans and plays a role in the pathogenesis of upper digestive tract diseases. In domestic animals, non-H. pylori Helicobacter species (NHPH) have also been discovered, which are frequently studied because of their zoonotic importance. This study aimed to investigate the occurrence of Helicobacter spp. in saliva and gastric samples from dogs. Furthermore, we evaluated the gastric bacterial colonisation density, presence of gastric lesions and sought to identify the main phylogenetic groups of the Helicobacter spp. isolated from domestic dogs in the central region of Rio Grande do Sul. This study included 20 dogs and the analysis employed were cytology, histopathology, polymerase chain reaction, rapid urease testing and phylogenetic analysis. Helicobacter spp. was present in the gastric mucosa of 17 of the dogs and saliva of 3 dogs. All asymptomatic dogs were positive for Helicobacter spp., whereas 2 dogs with chronic vomiting were negative. Density analysis of the gastric bacterial colonisation revealed that 3, 6 and 8 dogs had a mild, moderate and severe infection, respectively. Lymphocytic–plasmacytic infiltrates were the primary type of gastric lesions observed. However, the presence of Helicobacter and the density appeared to be unrelated to the gastric lesions found. The samples possessed a high nucleotide identity with remarkably similar sequences among some of the species of NHPH such as H. heilmannii s.s., H. salomonis, H. felis and H. bizzozeronnii. In the dogs, increased density, occurrence rate and predominance of NHPH of zoonotic importance were found in the stomach with a lower occurrence of Helicobacter spp. in the saliva. The saliva of domestic dogs, even of those without gastric colonisation, can cause Helicobacter infection in humans and other animals.